Pre-infarction Angina: Time Interval to Onset of Myocardial Infarction and Comorbidity Predictors - Sotomi, Yohei; Ueda, Yasunori; Hikoso, Shungo; Okada, Katsuki; Dohi, Tomoharu; Kida, Hirota; Oeun, Bolrathanak; Sunaga, Akihiro; Sato, Taiki; Kitamura, Tetsuhisa; Mizuno, Hiroya; Nakatani, Daisaku; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims As part of efforts to identify candidates for patient education aimed at decreasing mortality from acute myocardial infarction, we investigated the prevalence of pre-infarction angina and its predictors among comorbidities in patients who were hospitalized with acute myocardial infarction (MI). Methods We conducted a prospective multicenter observational registry of MI patients from 1998 to 2014 (N = 12,093). The present study investigated the prevalence of pre-infarction angina and its predictors among comorbidities with a logistic regression model. Pre-infarction angina was defined as chest pain/oppression observed within 1 month before the onset of MI but which lasted <30 min. Results After excluding 976 (8.1%) patients with missing data on pre-infarction angina, 11,117 patients [66.4 ± 12.0 years, 9,096 (75.2%) male] were analyzed. Of these, 5,428 patients (48.8%) experienced pre-infarction angina before the onset of MI, while 5,689 (51.2%) experienced sudden onset of acute MI. Most patients experienced the first episode of angina >6 h before the onset of MI, while 15% did so ≤6 h before. Patients with hypertension, diabetes, dyslipidemia, or a family history of MI had a higher probability of pre-infarction angina than those without. Elderly patients and those with a history of cerebrovascular disease were less likely to experience pre-infarction angina. Conclusions Almost half of MI patients in our registry experienced pre-infarction angina before MI onset. Patients with hypertension, diabetes, dyslipidemia, or a family history of MI had a higher probability of experiencing pre-infarction angina than those without.